Introduction: The harbour seal (Phoca vitulina) - a global perspective - Bjørge, Arne; Desportes, Geneviève; Waring, Gordon T; Rosing-Asvid, Aqqalu (NAMMCO Scientific Publications, 2010)
Introduction to Volume 8: Harbour seals in the North Atlantic and the Baltic